Public Behavior Awareness of Eradicating Mosquito Larvae in Kelambir Village, Pantai Labu District - Sahrial Sahrial; Ridha Panalia Siregar; Mira Indah Pratiwi Limbong; Mira Ulfa Yani Harahap; Muhammad Subhan; Muharrammah Isnaini; Nabila Husna; Nabilla Yurisna Siregar; Rizka Soraya Hasibuan; Romi Zahir Manik (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
The existence of Aedes aegypti mosquito larvae that cause dengue fever is caused by the existence of water reservoirs which play a very important role in the density of the Aedes aegypti mosquito vector because the more adequate water reservoirs, the more places Aedes aegypti mosquito larvae can breed. This study aims to discover how the community's knowledge, attitudes, and actions are related to the presence of Aedes aegypti mosquito larvae in Kelambir Village, Pantai Labu District. This research method is a qualitative descriptive study with a population of hamlet I and three kelambir villages. The sample number was 50 respondents with a simple random sampling technique. The results of the study revealed that out of 50 respondents, 32 respondents (64%) had good knowledge, 18 respondents (36) had less knowledge, 29 respondents (58%) had a good attitude, and 21 respondents (42%) had a poor attitude. Twenty-three respondents (46%) lack practice, 27 respondents (54%) have good practice; it is concluded that good knowledge and mosquito larvae are 32 respondents (64%) have a good attitude, and 29 respondents (58%) and good actions. There were larvae as many as 27 respondents (54%).Iit is expected to increase awareness further as well as good and correct actions in overcoming the problem of mosquito larvae which is the cause of the onset of DHF incidence in the community, such as implementing 3M and implementing a clean and healthy lifestyle.Local Government to utilize the results of this study in making a policy for mosquito larvae eradication efforts that are more in-depth and can provide solutions to solving the problem of dengue cases and dengue fever mosquito larvae breeding. It is expected to increase the comparison's awareness and validity to clarify further the research conducted